Overview of the Distribution of Tuberculosis (TB) Cases in Manado City, North Sulawesi Province, Indonesia - Selvi Safitri; Siska Shafrianti Pratiwi Darman (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Tuberculosis (TB) is one of the oldest infectious diseases and remains a major global public health challenge. The disease is caused by infection with Mycobacterium tuberculosis and can affect various organs of the body, although it most commonly involves the lungs. TB is transmitted through airborne mechanisms, whereby the bacteria are dispersed in droplet nuclei measuring approximately 1–5 microns when an infected individual coughs, sneezes, or speaks. Due to its mode of transmission and prolonged course, TB continues to pose a significant burden on urban populations. Objective: This study aims to describe the incidence of tuberculosis in Manado City, North Sulawesi Province, during the period 2021–2024. Specifically, the study presents the annual number of reported TB cases based on official data issued by the Central Statistics Agency, with the objective of providing an overview that may support the identification of potential risk factors. Method: A quantitative descriptive approach was employed to examine patterns of TB incidence in Manado City. The study design focused on providing a systematic, factual, and accurate description of the observed phenomenon without manipulating any variables. Secondary data were used to analyze temporal trends in TB incidence. Results: The findings indicate that TB incidence in Manado City increased from 2021 to 2023. This upward trend may be associated with factors such as limited public knowledge, smoking behavior, and alcohol consumption. However, a decline in TB cases was observed in 2024. Conclusion: The distribution of TB incidence in Manado City from 2021 to 2024 demonstrates a rising trend followed by a subsequent decline. Although the reduction in cases in 2024 is encouraging, it underscores the need for continuous evaluation of TB control strategies. A comprehensive understanding of factors contributing to increased TB incidence is essential for developing more effective and sustainable intervention programs.